Multi-modal emotional analysis in customer relation management and enhancing communication through integrated affective computing - W. Gracy Theresa; C. Pabitha; K. Revathi; Pornpimol Chawengsaksopark; Mithilesh Sathyanarayanan (Scientific Reports)
Abstract An important part of customer relationship management (CRM) is being able to read emails for emotional cues; this helps with both communication and keeping customers satisfied. This study aims to improve email emotion identification by creating a system combining visual clues, aural signals, and textual information. To analyze text and emoji, the system uses advanced affective computing techniques such as Robustly Optimized Bidirectional Encoder Representations from Transformers Approach (RoBERTa), Convolutional Neural Networks (CNN) for images, Bidirectional Convolutional Long Short-Term Memory (BiConvLSTM) for video, and Cross-Modal BERT for audio. Together, they enable a wider variety of emotional signals to be extracted and understood from email content, yielding more insightful results than text-based analysis could on its own. By facilitating better two-way communication and customer satisfaction, the technology intends to improve CRM by providing actionable information that firms can use to personalize responses. This research delves into the possible uses of multi-modal emotional analysis across different businesses dealing with customers and builds a strong foundation.